Institutionalizing the Employer Brand in Entrepreneurial Enterprises - Ta’Amnha, Mohammad (International Journal of Economics and Financial Issues, 2020)
Employer brand is defined as a package of psychological, functional, and economic benefits provided by employers to distinguish them from other firms. While employer brand is considered vital to the effectiveness of organizations, it has not been clearly operationalized, particularly in the entrepreneurial literature. This article employs institutional theory as the theoretical lens to study the EB concept in the entrepreneurial enterprise. The implications of institutional theory have demonstrated significant contributions to several issues concerning the entrepreneurship studies. Based on analyzing 40 semi-structured interviews with expert personnel from 13 entrepreneurial enterprises in Jordan finds that the three pillars of this theory (cultural-cognitive, normative-professional, and regulative) are crucial in institutionalizing an attractive employer brand. We contributed to the entrepreneurial literature by discussing the concept of entrepreneurial employer branding. This study offers practical implications to the entrepreneurial enterprise in respect of how they can become very attractive workplaces to their current qualified employees and to the qualified job seekers as well. Keywords: Entrepreneurial Enterprises, Institutionalizing, new institutional sociology theory, Employer Brand JEL Classifications: M00, M130, M510, M540 DOI: https://doi.org/10.32479/ijefi.10660